Molecular and Cellular Investigation of Malate:quinone oxidoreductases from Staphylococcus aureus - Gonçalves, Joana Lisboa da Silva (2019)
"Staphylococcus aureus are opportunistic pathogens and represent one of the most frequent causes for community acquired and nosocomial infections. Over time, S. aureus has developed several mechanisms which led to the selection of increasingly resistant strains. These potentially lethal bacterial pathogens have become a major public health threat, being urgent the development of new drugs against this worldwide problem. However, and intriguingly many fundamental aspects of S. aureus have escaped attention, such as its energy metabolism and respiratory enzymes. We aim to contribute to this knowledge by exploring malate:quinone oxidoreductases at molecular and cellular levels.(...)"